REVERSE LOGISTICS: THE PORTUGUESE COMPANIES' PERSPECTIVE - Gonçalves, Mélodine Fernandes (2016)
The Reverse Logistics has been object of great interest by the whole community. In Portugal, Reverse Logistics is an unfamiliar word in the business world. Due to this fact, that will be interesting to analyze and characterize the Portuguese companies’ perspective based on three aspects: The Concept, the Returns and the Environment. For this, semi structured interviews were applied to ten Portuguese companies of different dimensions and industrial sectors. The results showed all the large companies are aware of Reverse Logistics, the product returns strategies are reuse, sale to the scrap or recycling industries and the environment strategies mostly used by small and medium-size enterprise’s (besides waste recycling) are their reuse in the packaging of loads, and by large companies is directed towards recycling, planning routes and the use of recycled materials and reusable packaging. It is understood that, a lot of work in Reverse Logistics is still needed in the context, concerning the companies’ awareness to know all their logistics chain (forward and reverse) and in spite of the small and medium-size enterprise’s lack of knowledge of the this area, they practice some returns and environmental strategies, but still in a very incipient way.